Quinolone resistance in Salmonella enterica serovar Typhi: Mechanisms, factors driving the spread of resistance, current epidemiological trends and clinical significance - Gasim Omer Elkhalifa Abd-Elfarag (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2015)
The human restricted bacteria,Salmonella enterica serovar Typhi is the major cause of typhoid fever (or enteric fever), a characteristic severe systemic illness. In 2010, typhoid fever accounted for an estimated global burden of 27 million new cases and 200,000 deaths. For over two decades, S. enterica serovar Typhi and other serovars have developed resistance to the first line antimicrobials (ampicillin, chloramphenicol, and co-trimoxazole). As a result of this multidrug resistance (MDR), quinolones became key antibiotics for treatment of Salmonella Typhi disease. Quinolones are a group of antimicrobials with a 4-quinolone nucleus. Quinolones target the bacterial enzymes DNA gyrase and topoisomerase IV, which are essential for DNA replication and transcription.